Towards electrochemical iridium recycling in acidic media: effect of the presence of organic molecules and chloride ions. Issue 12 (9th March 2023) - Moriau, L.; Stojanovski, K.; Jovanovič, P.; Escalera-López, D.; Cherevko, S.; Hodnik, N.
Abstract : Green recycling of iridium made possible with the aid of organic compounds. Abstract : The utilization of iridium is expected to surge in the next few years, notably due to the rising implementation of water electrolyzer devices in the energy transition. However, the natural resources of this noble metal are extremely limited and thus its recycling will become of high importance. Unfortunately, iridium is also the most corrosion resistant platinum group metal, making its recovery from waste a difficult and energy-demanding process. Hereby, we study the impact of organics and chloride ions on the electrochemical dissolution of iridium in order to pave the way towards green recycling of this precious metal. We present a 40 times increased dissolution when cycling iridium in presence of HCl and 1 M ethanol compared to HClO4 . Our results point towards the direction of destabilizing Ir at relatively mild conditions in acidic media.